UPAYA PEMERINTAH DAERAH DALAM MENGATASI KEMISKINAN (Studi Kabupaten Solok Pasca Keluarnya UU NO. 32 Tahun 2004 tentang Otonomi Daerah ) (Jurnal Pelangi : Research of Education and Development, 2012)
AbstractThis research examines the effort of poverty alleviation in Solok. Solok isthe third highest poverty rate of 12 districts in West Sumatra (West Sumatra BPS2008). However, in the period 2008-2010 Solok successfully developed a varietyof efforts to improve welfare and increase their local revenue. Poverty is a socialproblem that is ingrained in Indonesia. Alleviate poverty is not just a matter forcentral government but also local governments and with the regional autonomy.This research to describe the efforts taken by the government Solok inovercoming poverty in the region. The methods uses qualitative, with the type ofdescriptive research that led to the situation that occurs through the dataobtained. This research includes the study of economic sociology and sociology ofdevelopment.The results showed that there were some efforts made by the governmentin addressing poverty Solok namely 1) local economic development by providingtraining and skills to the poor. 2) empowerment of micro, small and mediumenterprises in the form of rural development programs of economic institutions orvillages, by providing capital assistance in the form of money to poor people whohave good business in agriculture, fisheries, animal husbandry, trade andindustry. 3) Community development focused on the fulfillment of basic rights tohealth care for the poor because it will affect the health of someoneearning. Health program is using the funds the district budget. Budgeted funds arefrom the health centers to hospitals. Community can perform basic medicaltreatment for free. Government programs to alleviate poverti Solok is alsosupported by a free ID card program.